Kytococcus schroeteri Bacteremia in a Patient with Hairy Cell Leukemia: A Case Report and Review of the Literature - Akshay Amaraneni; Devin Malik; Sakshi Jasra; Sreenivasa R. Chandana; Deepak Garg (Case Reports in Infectious Diseases)
The Kytococcus genus formerly belonged to Micrococcus. The first report of a Kytococcus schroeteri infection was in 2002 in a patient diagnosed with endocarditis. We report a case of central line associated Kytococcus schroeteri bacteremia in a patient with underlying Hairy Cell Leukemia. Kytococcus schroeteri is an emerging infection in the neutropenic population and in patients with implanted artificial tissue. It is thought to be a commensal bacterium of the skin; however, attempts to culture the bacteria remain unsuccessful. There have been a total of 5 cases (including ours) of K. schroeteri bacteremia in patients with hematologic malignancies and neutropenia and only 18 documented cases in any population. Four of the cases of bacteria in neutropenic patients have been fatal, but early detection and treatment could make a difference in clinical outcomes.